‘A random assembly of geometric forms’: Thing Theory in J. G. Ballard's and Ray Bradbury's short stories - Tereszewski, Marcin (Orbis litterarum, 2024)
Thing Theory is a relatively new field of research, developed largely by Bill Brown on the basis of an already existing new materialist movement with roots reaching back to Martin Heidegger's interrogation of the ontology of things in ‘Das Ding’. Focusing on the interconnectedness of objects, their modes of being and irreducible ‘thingness’, as well as the agency objects are shown to exert when freed from the constraints of a subject‐centred perspective, this article presents a reading of three short stories by J. G. Ballard and Ray Bradbury which showcase how such issues are navigated in narrative form. Of particular interest for this article is the subject–object relationship, and the notion of ‘thingness’ as developed in Thing Theory in relation to the unique role accorded to the environment and inanimate objects in J. G. Ballard's and Ray Bradbury's selected works of fiction. It will be shown that a common theme connecting these works is the presence of a confrontation with the external world as it exists outside the definitions imposed on it by human subjects.